Motivation in Foreign Language Classrooms “An Overview of Motivational Strategies from Gardner to Dornyei” - Khouni, Warda (Sciences humaines; Vol. 22 (2011): SCIENCES HUMAINES)
الهدف من هذه الورقة البحثية هو التعريف بظاهرة التحفيز أي ماهيتها، مصادرها والعوامل المؤثرة فيها.  كما تقدم الدراسة أهم استراتيجيات التحفيز التي ظهرت في مجال علم النفس التربوي والتحفيز في تدريس اللغات الأجنبية ابتداء من المناهج القديمة مثل نموذج ڤاردنر  إلى أن نصل إلي الاستراتيجيات الحديثة في مجال التحفيز مثل منهاج زلتن دورني .  ونتمنى في آخر هذا البحث أن نكون قد ذكّرنا أساتذة اللغات الأجنبية بأهمية وضرورة استراتيجيات التحفيز، والعوامل المؤثرة في تحفيز متعلمي اللغات الأجنبية وتطبيق الاستراتيجيات حسب احتياجات الطلبة واهتماماتهم .           The aim of this paper is to examine and discuss the nature of motivation in foreign language learning, i.e. definition, sources and factors that affect motivation. Also, we aim to introduce   an overview of models studied in the field of language learning motivation, starting from earlier models such as Gardner’s until the latest ones like Dornyei’s framework. By the end of this exploratory study, we hope raise teachers’ awareness about the main factors that affect students’ motivation and about research done on motivation, then apply strategies that fit the needs of our students and classrooms